2021
DOI: 10.1088/1757-899x/1173/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic flame retardants’ efficacy of Aluminum Hydroxide, Magnesium Hydroxide in the combustion rate of intermediate Calamagrostis from Ecuador’ Moorlands

Abstract: In this research, intermediate calamagrostis vegetal fiber (FIC) combined samples were carried out in combination with polyester resin (RP), Aluminum Hydroxide (HA) and Magnesium Hydroxide (MH). The aim of this study is to determine inorganic flame-retardant effectiveness in the intermediate calamagrostis’ combustion rate reduction from Ecuador’s moorlands and possible forest fires’ control of this endemic plant species. The flammability index was obtained following the ISO 3795 standard; In addition, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Los tratamientos con ignífugos inorgánicos reducen el tiempo que tardan los materiales en encenderse y quemarse al entrar en contacto con el fuego, mejorando sus reacciones y proporcionando más tiempo para que las personas escapen o sean rescatadas en caso de quedar atrapadas en un espacio confinado. El Hidróxido de Aluminio Al(OH) e Hidróxido de Magnesio Mg(OH)2 son retardantes comunes utilizados para mitigar los incendios, y se pueden aplicar en diversas superficies combustibles (Córdova-Suárez et al, 2021). Aunque estos esfuerzos se han centrado en la reducción de costos, los materiales ignífugos se utilizan desde hace varias décadas.…”
Section: Introductionunclassified
“…Los tratamientos con ignífugos inorgánicos reducen el tiempo que tardan los materiales en encenderse y quemarse al entrar en contacto con el fuego, mejorando sus reacciones y proporcionando más tiempo para que las personas escapen o sean rescatadas en caso de quedar atrapadas en un espacio confinado. El Hidróxido de Aluminio Al(OH) e Hidróxido de Magnesio Mg(OH)2 son retardantes comunes utilizados para mitigar los incendios, y se pueden aplicar en diversas superficies combustibles (Córdova-Suárez et al, 2021). Aunque estos esfuerzos se han centrado en la reducción de costos, los materiales ignífugos se utilizan desde hace varias décadas.…”
Section: Introductionunclassified
“…Different studies have shown that the addition of Mg(OH) 2 and Al(OH) 3 fillers are able to significantly improve the flame retardant features of coatings, leading to a decrease in the heat release rate, smoke production, and an increase in the ignition time of the composite coating [10][11][12].…”
Section: Introductionmentioning
confidence: 99%